2021
DOI: 10.1186/s43066-020-00067-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphisms and risk of hepatocellular carcinoma in hepatitis C-related liver cirrhosis

Abstract: Background HCV is a major risk factor for HCC; however, the exact mechanism of hepatocarcinogenesis is still not fully understood. Host genetic factors have been reported to play a significant role. Experimental studies support the tumor inhibitory effect of vitamin D on HCC cells. Several single nucleotide polymorphisms (SNPs) have been depicted in the vitamin D receptor (VDR) gene. We aimed to assess whether any of these polymorphisms could be significantly associated with increased risk of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Our results are consistent with a number of studies demonstrating that the ApaI aa genotype is associated with progressive liver disease or the development of HCC in CHC [ 18 , 42 - 45 ], and even claiming that it could serve as a genetic marker to predict the risk of HCC in this setting [ 43 ]. Mohammed et al showed that an advanced stage of liver cirrhosis, lower serum concentrations of cholecalciferol and the occurrence of HCC were more frequent in patients carrying the dominant (Aa/aa) allele of the ApaI SNP [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with a number of studies demonstrating that the ApaI aa genotype is associated with progressive liver disease or the development of HCC in CHC [ 18 , 42 - 45 ], and even claiming that it could serve as a genetic marker to predict the risk of HCC in this setting [ 43 ]. Mohammed et al showed that an advanced stage of liver cirrhosis, lower serum concentrations of cholecalciferol and the occurrence of HCC were more frequent in patients carrying the dominant (Aa/aa) allele of the ApaI SNP [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…HCC is also known to be more common in men, and numerous SNPs have been linked to a higher genetic susceptibility to the disease [43]. In this study, there was no signi cant association between VDR SNPs (rs2228570 and rs3782905) and smoking status in HCC risk, which agreed with Galal et al, [22]. However, the GG genotype of DBP (rs7041) SNP was signi cantly associated with disease progression with both groups (non-smokers and smokers).…”
Section: Discussionsupporting
confidence: 91%
“…Few VDR SNPs have been examined concerning HCC risk factors in the Egyptian population [22,23], and it is still unclear in Egyptian patients whether DBP SNPs could be a risk factor for chronic liver diseases. As a result, this study aims to determine the signi cance of the VDRs (rs2228570, rs3782905, rs11568820) and DBP (rs7041) for the susceptibility to HCC in Egyptian patients with chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between HCV and HCC is well established, it is still unclear and poorly understood how directly HCV causes cancer. The interaction between environmental, viral, and host cofactors may result in multiple genetic alterations which gradually accumulate in hepatocytes leading to the development of HCC [ 3 ]. It is well known that metabolic derangements, such as adipokine imbalance, are associated with the development of cancer, including HCC [ 2 ].…”
Section: Introductionmentioning
confidence: 99%